Tapered plastic optical fiber coated with single wall carbon nanotubes polyethylene oxide composite for measurement of uric acid concentration - Batumalay, Malathy; Ahmad, F.; Lokman, A.; Jasim, Ali Abdulhadi; Harun, Sulaiman Wadi; Ahmad, Harith (Emerald, 2014)
Purpose – A simple tapered plastic optical fiber (POF) sensor is proposed and demonstrated for measurement of uric acid concentrations in de-ionized water. The paper aims to discuss these issues.